EXTRACTION OF ANTIMICROBIAL COMPOUNDS FROM PSIDIUM GUAJAVA LEAVES AND THEIR APPLICATION IN SOAP FORMULATION WITH AZADIRACHTA INDICA SEED OIL - Muhammad, Ismail; Mashi, Ahmed Lawal (FUDMA Journal of Sciences, 2025)
The search for sustainable antimicrobial agents has led to increasing interest in bioactive compounds from medicinal plants. This study investigated the extraction of antimicrobial compounds from Psidium guajava leaves and their application in soap formulation with Azadirachta indica (neem) seed oil. Phytochemical screening revealed the presence of phenols, tannins, flavonoids, terpenoids, glycosides, and saponins. Maceration of 50 g of guava leaves yielded 10.68 g of methanolic extract compared to 9.65 g with ethanol, indicating higher efficiency of methanol extraction. FTIR spectra of guava leaf extracts identified functional groups such as O–H stretching (3250.20 cm⁻¹), C=O stretching (1689.30 cm⁻¹), and aromatic C=C stretching (1602.80 cm⁻¹), while neem seed oil exhibited C=C unsaturation (1654.90 cm⁻¹) and O–H stretching (3369.50 cm⁻¹), confirming the presence of phenolic compounds, flavonoids, and unsaturated fatty acids. Performance analysis of guava leaf soap (GLS) showed formability of 10.70 cm, pH of 10.80, and hardness index (needle penetration) of 3.10 cm, comparable to commercial Dudu Osun soap (formability 11.10 cm, pH 9.45, hardness 2.90 cm). Antimicrobial assays demonstrated that GLS inhibited Staphylococcus aureus (19.00 mm), Bacillus aureus (17.50 mm), Aspergillus niger (18.00 mm), and Candida albicans (18.00 mm) at 500 mg/mL, with inhibition zones statistically comparable to those of Dudu Osun (18.00–20.50 mm). These findings confirm that guava leaf extracts and neem oil can be effectively harnessed for antiseptic soap production, providing a natural, cost-effective alternative to synthetic formulations with demonstrated antibacterial and antifungal activity.
Keywords: Psidium guajava; Azadirachta indica; Soap formulation; FTIR characterization; Antimicrobial activity